Enhanced enzymatic delignification of oil palm biomass with ionic liquid pretreatment - Financie, R. (Elsevier, 2016)
The enzymatic delignification of lignocellulosic biomass for separation of cellulose, Earth's most abundant biopolymer, has been generally acknowledged as an environmentally friendly process. However, this approach for lignin degradation has been found to be very slow due to the difficulties in enzyme accessibility to the solid substrate. To address this issue, this paper reports a delignification process of oil palm frond biomass (OPFB) that combined an ionic liquid (IL) pretreatment (dissolution and recovery of treated OPFB by anti-solvent), followed by enzymatic delignification. The pretreatment of biomass was conducted using a hydrophilic IL EMIMDEP (1-ethyl-3-methylimidazolium diethyl phosphate), which possesses very high solubility for lignocellulosic biomass. Pretreated and untreated materials were characterized by scanning electron microscope, Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and chemical methods. IL pretreatment significantly enhanced the rate of enzymatic delignification of OPFB. The lignin content of produced materials was about 8.5 wt%, much lower than 24.0 wt% lignin content of untreated OPFB materials. Obtained cellulose-rich OPFB fibers exhibited higher thermal stability compared to untreated OPFB, possibly due to removal of lignin. These results indicate that IL pretreatment may provide unique advantages to separation of cellulose rich OPFB fibers for composite, textile and other industrial applications. Â© 2016 Elsevier B.V.